Achieving Social Skills From The Perspective Of Self- Concept In The Gifted Individual. A Field Study On A Sample Of Gifted Middle School Students In Ghardaïa (مجلة الواحات للبحوث والدراسات, 2025)
The article aims to determine the level of self-concept and the level of social skills, examine the relationship between them, and highlight the differences according to the variables of gender (males, females) and family type (extended, nuclear) among a sample of gifted middle school students in Ghardaïa.      The descriptive approach was used on a sample of 112 students, divided into 34 as a pilot sample and 78 as a main sample. The sample was identified using a teacher nomination form developed by Mekhout Fatiha (2020) and the Renzulli Scale for Gifted Characteristics (2017) across three middle school levels (grades 2, 3, and 4) in educational institutions (public, private, and independent) in  Ghardaïa, distributed across the following middle schools: Tawenza Scientific School, Al-Islah Institute for Girls (Hawasha Branch), Sheikh Ammi Said Institute (Belghenam), Al-Nour Quranic School for Girls, and Imam Rabie bin Habib School. The study tools consisted of the Self-Concept Scale developed by the researcher " Rabie Louahadj" (2021) and the Social Skills Scale developed by "Abdul Rahman Mohamed Al-Sayed" (1998). The study concluded that there is a correlational relationship between self-concept and social skills, and that there are no significant differences between the two concepts attributed to the variables of gender or family type.Keywords: self-concept, social skills, gifted